2013
DOI: 10.4236/ajps.2013.410250
|View full text |Cite
|
Sign up to set email alerts
|

Rt-PCR Analysis and Evolutionary Relationship of Some Hungarian <i>Grapevine leafroll associated virus</i> 1 and 3 Isolates

Abstract: Hungarian isolates of Grapevine leafroll associated virus 1 and 3 (GLRaV-1, GLRaV-3) were tested using serological (DAS-ELISA) and molecular (RT-PCR) methods. Five hundred bp long PCR products of the part of HSP70 gene of one serologically positive GLRaV-1 and four GLRaV-3 isolates were sequenced. These sequences were applied for phylogenetic analysis and compared to foreign virus isolates of NCBI GenBank. Phylogenetic analysis of GLRaV-1 HSP70 gene supported the earlier results that it could be divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…According to Kominek et al (2005) this cluster can be separated into two groups that were designated as groups A and E however Alabi et al (2011) reported three distinct variant groups and they could not found any evidence for precisely defined geographical structuring of GLRaV-1 isolates among the three groups. Our phylogenetic analysis of GLRaV-1 HSP70h gene is corresponded to the results of Kominek et al (2005) and Cseh et al (2013) regarding the number of the phylogroups however no correlation was found for Alabi et al (2011). The cell to cell movement protein, which is HSP70 gene product, has highly conserved sequence among Closteroviridae family members (Dolja et al 1994).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…According to Kominek et al (2005) this cluster can be separated into two groups that were designated as groups A and E however Alabi et al (2011) reported three distinct variant groups and they could not found any evidence for precisely defined geographical structuring of GLRaV-1 isolates among the three groups. Our phylogenetic analysis of GLRaV-1 HSP70h gene is corresponded to the results of Kominek et al (2005) and Cseh et al (2013) regarding the number of the phylogroups however no correlation was found for Alabi et al (2011). The cell to cell movement protein, which is HSP70 gene product, has highly conserved sequence among Closteroviridae family members (Dolja et al 1994).…”
Section: Resultssupporting
confidence: 52%
“…RNA viruses, such as GLRaVs, have high ratio of genetic diversity due to an error-prone replication with high mutation rates; therefore, the evolutionary processes which allow them to spread throughout the species need to be clarified (Fazeli & Rezaian 2000). Although GLRaV-1 is a common virus infecting grapevine plants worldwide, limited information is available in literature about the genomic variability and molecular evolution of GLRaV-1 (Little et al 2001;Kominek et al 2005;Alabi et al 2011;Predajna et al 2013;Cseh et al 2013;Fan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The same groups were dominant in Portugal (Gouveia et al 2011). Prevalence of variant group II is reported from South Africa (Jooste et al 2011), Spain (Pesqueira et al 2016), and Hungary (Cseh et al 2013), while Napa Valley (Sharma et al 2011), China (Farooq et al 2012), and New Zealand ) are dominated by group I. Mixed infections with both variants were present in 20 GLRaV-3 positive vines (45.5%), significantly more than the 25.3% reported from Portugal (Gouveia et al 2011) or 22% from Napa Valley (Sharma et al 2011).…”
Section: Discussionmentioning
confidence: 91%
“…They clustered together with isolates from Brazil, Israel, and South Africa, but share only 90–91% identity with European strains. Their phylogenetical relationship based on the HSP70 region showed that they cluster into two distinct group together with isolates from different regions of the country (Cseh et al, 2013 ) (Supplementary Figure 2D ). Samples 14_MK1 and 15_MK3 are different varieties in different rows of the same plantation.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis of our isolates showed that they clustered into two distinct groups, the same E and A as was suggested by Kominek et al ( 2005 ) (Supplementary Figure 2B ) and are only 82–92% identical to the reference genome, supporting the operation of high-level variability, due to which GLRaV1 can be easily overlooked by traditional diagnostic methods (Esteves et al, 2013 ). The only Hungarian GLRaV1 isolate (CSE_6.4.1.H) in GenBank (Cseh et al, 2013 ) (clustered to group E) was collected at the same region of the country from where HUTK and HUHT (clustered to group A) originated, suggesting that the source of the infection is more likely the propagation material. These results show that detection of GLRaV1 by sRNA NGS seems reliable, but its validation by RT-PCR may be problematic due to the high variability of the virus.…”
Section: Resultsmentioning
confidence: 99%